HUMAN RESOURCE MANAGEMENT, WORK EFFECTIVENESS EMPLOYEE - AR, Khorida; Nurhaeni, Siti; Devianti, Reinna; Muljadi, Muljadi (Dynamic Management Journal, 2025)
This study aims to analyze human resource management strategies in improving employee work effectiveness at PT. Tranciv Global Perkasa. Employee work effectiveness is one of the key factors in achieving the company's goals. This research employs a qualitative approach with a descriptive method, where data were obtained through in-depth interviews with relevant informants. The results indicate that the implemented human resource management strategies include planning, recruitment, selection, employee placement based on competencies, and employee development through training and workshops. Furthermore, performance-based rewards and compensation policies are key measures taken by the company to motivate and enhance employee loyalty. The employee performance evaluation system is conducted periodically to ensure optimal work effectiveness. This study concludes that integrated and adaptive human resource management significantly contributes to improving employee work effectiveness and the company’s competitiveness. The author suggests that performance evaluations be conducted more frequently, every three months, to monitor employee performance progress more effectively and enhance work motivation through a competitive reward system.